First and second step characteristics of amputee and able-bodied sprinters - Strutzenberger, G.; Brazil, A.; Exell, T.; von Lieres und Wilkau, H.; Davies, J. D.; Willwacher, S.; Funken, J.; Müller, R.; Heinrich, K.; Schwameder, H.; Potthast, W.; Irwin, G. (International Journal of Sports Physiology and Performance, 2018)
Context: In sprint events, the first 2 steps are used to accelerate the center of mass horizontally and vertically. Amputee athletes cannot actively generate energy with their running-specific prosthesis. It is likely that sprint acceleration mechanics, including step asymmetry, are altered compared with able-bodied athletes. Purpose: To investigate spatiotemporal and kinetic variables of amputee compared with able-bodied sprinters. Methods: Kinematic and kinetic data of the first and second stance were collected from 15 able-bodied and 7 amputee sprinters (2 unilateral transfemoral, 4 unilateral transtibial, and 1 bilateral transtibial) with a motion-capture system (250 Hz) and 2 force plates (1000 Hz). In addition, bilateral asymmetry was quantified and compared between groups. Results: Compared with able-bodied athletes, amputee athletes demonstrated significantly lower performance values for 5- and 10-m times. Step length, step velocity, and step frequency were decreased and contact times increased. Peak horizontal force and relative change of horizontal velocity were decreased in both stances. Peak vertical force and relative change of vertical velocity were lower for the amputee than the able-bodied group during the first stance but significantly higher during the second stance. During the first stance, able-bodied and amputee sprinters displayed a similar orientation of the ground-reaction-force vector, which became more vertically orientated in the amputee group during second stance. Amputee sprinters showed significantly greater asymmetry magnitudes for vertical force kinetics compared with able-bodietd athletes. Conclusion: A running-specific prosthesis does not replicate the function of the biological limb well in the early acceleration phase.